Optimizing Promoters and Subcellular Localization for Constitutive Transgene Expression in Marchantia polymorpha. - Tse, Sze Wai; Annese, Davide; Romani, Facundo; Guzman-Chavez, Fernando; Bonter, Ignacy; Forestier, Edith; Frangedakis, Eftychios; Haseloff, Jim (Oxford University Press (OUP), 2024)
Marchantia polymorpha has become an important model system for comparative studies and synthetic biology. The systematic characterization of genetic elements would make heterologous gene expression more predictable in this test bed for gene circuit assembly and bioproduction. Yet, the toolbox of genetic parts for Marchantia includes only a few constitutive promoters that need benchmarking to assess their utility. We compared the expression patterns of previously characterized and new constitutive promoters. We found that driving expression with the double enhancer version of the cauliflower mosaic virus 35S promoter (pro35S × 2) provided the highest yield of proteins, although it also inhibits the growth of transformants. In contrast, promoters derived from the Marchantia genes for ETHYLENE RESPONSE FACTOR 1 and the CLASS II HOMEODOMAIN-LEUCINE ZIPPER protein drove expression to higher levels across all tissues without a growth penalty and can provide intermediate levels of gene expression. In addition, we showed that the cytosol is the best subcellular compartment to target heterologous proteins for higher levels of expression without a significant growth burden. To demonstrate the potential of these promoters in Marchantia, we expressed RUBY, a polycistronic betalain synthesis cassette linked by P2A sequences, to demonstrate coordinated expression of metabolic enzymes. A heat-shock-inducible promoter was used to further mitigate growth burdens associated with high amounts of betalain accumulation. We have expanded the existing tool kit for gene expression in Marchantia and provided new resources for the Marchantia research community.
Keywords: Marchantia polymorpha; Betalain; Metabolic engineering; Promoter; Recombinant protein; Synthetic biology; Marchantia; Promoter Regions, Genetic; Gene Expression Regulation, Plant; Transgenes; Plants, Genetically Modified; Plant Proteins; Caulimovirus